Daidzein Alleviates Hypothalamic-Pituitary-Adrenal Axis Hyperactivity, Ameliorates Depression-Like Behavior, and Partly Rectifies Circulating Cytokine Imbalance in Two Rodent Models of Depression - Chen, Long; Wang, Xiaokun; Zhang, Yunpeng; Zhong, Hequan; Wang, Cuiting; Gao, Pengfei; Li, Bing (Frontiers in Behavioral Neuroscience, 2021)
Depression is one very common mental health disorder which can cause morbidity and mortality if not addressed. Recent studies have provided strong evidence that depression may be accompanied by immune activation, secondary inflammatory-reaction and hyperactivity of Hypothalamic pituitary adrenal (HPA) axis. It is well-known that it takes at least two weeks for the conventional antidepressants, especially (Selective serotonin reuptake inhibitors) SSRIs, to produce effects. To better understand the mechanism of antidepressant effects on depression and subsequently further elucidate pathogenesis of depression, we selected daidzein to observe its effects on the depression-like and anxiety-like behavior in two different rodent models of depression which were induced by learned helplessness and chronic mild stress and then simultaneous evaluation of the depression-like behavior, activity of HPA axis and circulatory cytokines were.  Our results showed that daidzein attenuated depression-like behaviors through alleviating HPA axis hyperactivity, decreasing the levels of stress-related hormones and some inflammatory cytokines in both two rodent models of depression.